Instituições e Cultura: difusão e modelagem internacional da política pública brasileira de combate à pobreza - Samira Kauchakje (Universidade do Vale do Rio dos Sinos (UNISINOS), 2013)
This article aims to present the results of research that investigates social policies for poverty reduction of the Cardoso, Lula and Rousseff terms of office from the perspective of theoretical currents on international modeling and Policy Diffusion. The methodology is in the exploratory phase and in the discussion there is data related to the significant moments of the Brazilian social protection system between the years 1995 and 2012. The results suggest that in the terms of Cardoso, Lula and Rousseff the so-called “posi- tive” modeling (isomorphism) predominated due to the adherence of national policies to international policies focusing on the low-income population and also due to the fact that Brazilian monetary transfer policies were recently considered by the international political community as a model. On the other hand, in Lula’s second term and in Rousseff’s period there is the negative modeling identified in the linkage between economic growth policies and the increase or the maintenance of the values of social public spending. This is contrary to international financial institutions recommendations that prescribe austerity in reducing social public policy.